The Relationship Between Water and Sediment Quality on Mangrove Growth in Panimbang District, Banten Province - Fairuz, Najla Tasya; Irnawati, Ririn; Khalifa, Muta Ali; Susanto, Adi; Nurdin, Hery Sutrawan; Munandar, Erik; Syafrie, Hendrawan; Alansar, Toufik; Sulistyono, Bakti; Raihan, Ahmad (Agrikan Jurnal Agribisnis Perikanan, 2024)
The coastal area of Panimbang, severely impacted by the 2018 Sunda Strait tsunami, has been the focus of rehabilitation due to its vulnerability from the absence of natural barriers like mangroves, which are crucial in mitigating tsunami effects. Through the Mangrove Blue Carbon program, 10,000 mangrove seedlings were planted in Panimbang Jaya Village to restore the coastal ecosystem. This study evaluates the relationship between sediment characteristics and mangrove growth. Measurements included water quality (temperature, pH, salinity), mangrove growth indicators (height, stem diameter, branch and leaf counts), and sediment characteristics (texture, organic carbon, nitrogen, and phosphorus). Results showed water quality supported mangrove growth. Temperature increased from 30.96°C (2023) to 32.6°C (2024) due to El Niño but remained within tolerance limits. pH rose from 7.54 to 8.02 (optimal 6–9), and salinity increased from 16.66‰ to 19.34‰ (tolerance 10–30‰). Sediment texture was predominantly sandy (>90%) with low fertility, indicated by organic carbon (1.5–3.2%), nitrogen (0.2–0.6%), and phosphorus (0.01–0.04%). Mangrove growth improved significantly, with height increasing from 120–150 cm to 160–210 cm, stem diameter from 2.0–3.2 cm to 3.5–4.8 cm, branch count from 5–8 to 8–12, and leaf count from 20–35 to 35–50. Mangrove growth correlated with clay texture and carbon-rich sediment despite low fertility, while optimal water quality still supported their. This emphasizes the need for ongoing monitoring and sustainable rehabilitation efforts to ensure the success of ecosystem restoration.